Microwave-Assisted Cocrystallization of p-Methoxycinnamic Acid with Saccharin and Nicotinamide: Comparative Effects on Solubility and Dissolution - Paramanandana, Abhimata; Kawaguchi , Kurnia; Sulistyowaty, Melanny Ika; Setyawan, Dwi; Almaghrabi, Marey (Science and Technology Indonesia, 2026)
p-methoxycinnamic acid (pMCA) has activity as an anti- inflammatory and analgesic but is difficult to dissolve in water with a solubility of only 0.712 mg/mL at 25 oC. Poor solubility will result a low dissolution rate so that drug absorption becomes limited, affects the bioavailability, and causes therapeutic effect to become less optimal. The formation of co-crystals are able to improve the solubility properties and dissolution rate by physically modifying the active compound. Cocrystals are crystalline materials composed of two or more molecules at specific stoichiometric ratios to form non-covalent bonds. Both saccharin and nicotinamide can be use as coformers because saccharin and nicotinamide were able to increase the solubility and dissolution rate of active compounds due to the formation of non-covalent bonds. The results showed that the formation of cocrystals using the microwave radiation had a higher solubility and dissolution rate of pMCA compared to pure pMCA. The pMCA-nicotinamide cocrystal increased solubility 1.29 times higher than a single pMCA while the pMCA-saccharin cocrystal increased solubility only 1.26 times higher than a single pMCA. In the dissolution rate test, the pMCA-Nicotinamide cocrystal increased the dissolution rate 3.67 times higher while the pMCA-Saccharin only increased 3.55 times higher than a single pMCA. These results show that both cocrystals have better solubility and dissolution rate properties than pure pMCA so it can be said that forming cocrystals can increase the solubility and dissolution rate of pMCA. Based on this study findings, it can also confirm that formation cocrystal pMCA using nicotinamide coformers has agood solubility and dissolution rate than formation cocrystal using saccharin coformers.